Learning Motivation and Cognitive Development in Southeast Asian Students: A Bibliometric Analysis (2014-2024) - Hisyam syafii; Rudyn alaldaya; Oprimuriandy T.D. Putra (Educational Insights, 2025)
This study analyses research trends regarding students' learning motivation and cognitive development in Southeast Asia from 2014 to 2024 using bibliometric analysis. The study examines the necessity for an in-depth comprehension of the growth of educational psychology in this crucial location through the analysis of publishing trends, cooperation networks, and theme advancements. Employing quantitative bibliometric technique, data were gathered from the Scopus, Web of Science, and Google Scholar databases utilising systematic keyword combinations pertinent to learning motivation, cognitive development, and Southeast Asian nations. The investigation included co-occurrence mapping, temporal visualisation, and theme grouping with VOSviewer software. The findings indicate five primary thematic clusters that embody different theoretical views, illustrating a paradigmatic transition from neurobiological approaches (2014-2016) to contextual-pedagogical themes (2017-2019), ultimately leading to themes of digital-pandemic adaptability (2020-2024). The research delineates the confluence of Self-Determination Theory, Piaget's cognitive development theory, Vygotsky's social constructivism, and executive function theory into a cohesive framework. Prominent topics encompass cultural backdrop, linguistic development, and socioeconomic considerations, illustrating the distinctive complexity of Southeast Asia. The research illustrates the evolution from disparate disciplinary methods to a cohesive multi-theoretical framework, integrating achievement goal theory with growth mindset and the Technology Acceptance Model with self-regulated learning theory. These findings underscore the need for culturally sensitive and technology-enhanced educational techniques that utilise advancements in neuroscience and digital technologies to optimise student learning outcomes in the different socio-cultural contexts of Southeast Asia.